2010
DOI: 10.1016/j.exppara.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi: Biological characterization of a isolate from an endemic area and its susceptibility to conventional drugs

Abstract: We describe some biological and molecular characteristics of a Trypanosoma cruzi isolate derived from a Triatomine captured in Nicaragua. PCR based typification showed that this isolate, named Nicaragua, belonged to the lineage Tc I. Nicaragua infected culture cells were treated with allopurinol, showing different behaviour according to the cellular compartment, being cardiomyocyte primary cultures more resistant to this drug. The course of the infection in a mice experimental model and its susceptibility to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…A study of a TcI strain from Nicaragua showed the benefits of early BZ treatment, which led to significant reductions in parasitemia, mortality, and the number of parasites in the skeletal muscle during CP, but no significant differences were observed in the frequencies of lesions in the heart and smooth muscles of these mice. 38 The pathological changes observed with TcII confirm the results of previous studies that used TcII strains of different origins 8,[39][40][41] and from chronic patients in Paraná (Meza SKL and others, unpublished data). 34 The TcII parasites invade heart cell cultures in lower numbers than TcI parasites; however, intracellular multiplication of TcII parasites was more efficient than that of TcI parasites, strongly suggesting that intracellular development is important to determine parasite tissue tropism.…”
Section: Discussionsupporting
confidence: 79%
“…A study of a TcI strain from Nicaragua showed the benefits of early BZ treatment, which led to significant reductions in parasitemia, mortality, and the number of parasites in the skeletal muscle during CP, but no significant differences were observed in the frequencies of lesions in the heart and smooth muscles of these mice. 38 The pathological changes observed with TcII confirm the results of previous studies that used TcII strains of different origins 8,[39][40][41] and from chronic patients in Paraná (Meza SKL and others, unpublished data). 34 The TcII parasites invade heart cell cultures in lower numbers than TcI parasites; however, intracellular multiplication of TcII parasites was more efficient than that of TcI parasites, strongly suggesting that intracellular development is important to determine parasite tissue tropism.…”
Section: Discussionsupporting
confidence: 79%
“…8 As shown in Figure 2, treatments with BNZ-nps 25, 50 μg/mL and R-BNZ 50 μg/mL exhibited no significant differences in the percentage of amastigote growth inhibition on Vero and cardiac myocyte cells. It is worth mentioning that with half the dose of BNZ-nps, the same inhibitory effect on the growth of amastigotes is achieved.…”
Section: Resultsmentioning
confidence: 97%
“…19 Previously, it was observed that TcN epimastigotes DTU I were more resistant to BNZ than CL Brener epimastigotes DTU VI. 8 In this regard, although there are limits to determine the efficacy of BNZ, its affinity for cardiac tissue and resistance to BNZ makes it interesting to study these BNZ-nps in the isolated TcN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the significance of TcAKR activity in Bz metabolism, we studied TcAKR expression and its related enzymatic activities in two T. cruzi strains with differential susceptibilities to Bz: CL Brener and Nicaragua (24). CL Brener was more susceptible to Bz than Nicaragua, presenting IC 50 s of 10 and 20.5 M, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 99%